THE LEASE OF SOUND HOREG: A FIQH MUAMALAH PERSPECTIVE - Ihsan Helmi Lubis; Mu’adil Faizin; Muhammad Amin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the legality of the lease of sound horeg from a Fiqh Muamalah perspective. The widespread use of sound horeg in various community activities often gives rise to issues related to noise disturbance, damage to public and private property, public order, potential social conflict, health problems, and even death. In the context of Fiqh Muamalah, lease contracts (ijarah) are fundamentally permissible as long as they fulfill the prescribed pillars and conditions and do not contain elements of harm (maḍarrah). This research employs a literature study method with a normative-theological approach, examining Qur’anic evidence, hadith, and juristic maxims. The findings indicate that renting sound horeg is legally permissible (mubāḥ) when its implementation complies with the pillars and conditions of leasing. Conversely, if the use of sound horeg leads to harm—such as extreme noise (operating at volumes exceeding WHO standards/85 decibels for an 8-hour exposure duration), damage to public or private property, harm to auditory health, social conflict, disturbance of public order, destruction of marine ecosystems, or causing death to humans or marine life—then the leasing arrangement becomes impermissible. This prohibition is grounded in several Qur’anic verses, including Q.S. al-Baqarah 2:195, which forbids actions that endanger oneself or others; Q.S. al-Ahzāb 33:58, which prohibits causing harm to fellow believers without just cause; and Q.S. al-A‘rāf 7:74, which emphasizes the prohibition of spreading corruption on earth. It is also supported by Prophetic traditions forbidding actions that harm oneself or others, along with the warning that those who burden or endanger others will themselves be burdened and endangered by God. Moreover, several juristic maxims apply, such as lā ḍarar wa lā ḍirār, al-ḍarar yudfa‘ bi-qadri al-imkān, and dar’ al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ).